Practical implementation and impact of the 4R principles in ethnopharmacology: Pursuing a more humane approach to research - Liu, Jimin; Zai, Xiang; Tian, Xiaqing; Li, Jiaxuan; Yan, Shipeng; Wang, Taiyi (Frontiers in Pharmacology, 2025)
Ethnopharmacology, a discipline focused on studying the medicinal use of natural materials by humans, plays a crucial role in addressing challenges in modern drug development. However, the traditional 3R principle—Replacement, Reduction, and Refinement—have limitations in guiding the ethical management of animal experimentation, conducting animal studies, and utilizing animal-derived materials in ethnopharmacological research. To address these gaps, the field has introduced the 4R principles, which expand the original framework by adding “Responsibility.” The Responsibility principle highlights the ethical obligation of researchers to consider the welfare of experimental animals during all procedures. It calls for researchers to take accountability for their actions and decisions, ensuring that they actively protect animal welfare and exhibit empathy across species. This principle reinforces the ethical foundation of ethnopharmacological research. To implement the 4R principles effectively, this article explores the dimensions of Reduction, Refinement, Replacement, and Responsibility in detail. For Reduction, strategies include minimizing animal use by developing optimized, efficient experimental designs, creating tissue banks to recycle animal samples, and improving success rates in animal modeling. These efforts collectively aim to enhance ethical standards while advancing scientific outcomes. In terms of Refinement, the goal is to minimize animal distress and pain by improving the experimental environment, refining operational procedures, ensuring strict control of experiments under anesthesia, and prioritizing non-invasive or minimally invasive techniques for data collection. For Replacement, the aim is to reduce the need for experimental animals by exploring alternative solutions. This includes substituting in vitro experiments for in vivo ones, using 3D organoids to replace animal organs, and applying deep learning technologies in ways that decrease animal use. The Responsibility principle focuses on enhancing researchers’ ethical obligations toward animal welfare. This can be achieved by improving regulations and policies governing animal experimentation, providing ethical training for technical personnel, and promoting awareness of animal welfare and ethical practices. The introduction and implementation of the 4R principles provide valuable guidance for the ethical conduct of animal experimentation in ethnopharmacological research, offering new insights and methodologies that support the responsible use of animals in scientific studies.